An Reengineering the Management Model of Defense to Overcome Separatism in Papua for National Interests: Management Model Of defense - Harefa, Faonaso; Aritonang, Sovian; Supriyadi, Asep Adang; Harsono, Cecilia F. (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This research was made to determine the effect of defense management on national interests using the mixed methods approach. Qualitative data are analyzed using NVivo 12, while quantitative data uses SEM-PLS 4 software to obtain robust and reliable findings. The results showed that defense management reengineering had a significant effect on the realization of national interests in overcoming separatists in Papua. Cronbach’s alpha and composite reliability values ​​that show high internal consistency. Average Variance Extracted (AVE) of more than 0.50, confirming the convergence of good indicators. The evaluation of the structural model shows a significant relationship between the engineering management of defense and national interests (the path coefficient = 0.661, p-value = 0.000), with an R-square value of 0.437, which shows moderate influence. NVivo 12 analysis reveals a major factor in strengthening national interests, including logistical readiness, interoperability between units, and local communities in handling separatism. However, there are limitations such as budget constraints, multidimensional threat complexity, and lack of cross-sector coordination that hamper optimal implementation. Importance-Performance Map Analysis (IPMA) shows that although engineering management of defense has a significant effect on national interests, its performance still needs to be improved. This study contributes originality by integrating SEM-PLS and NVivo to provide a holistic perspective and emphasize the need for more adaptive defense reengineering management to increase the effectiveness of defense strategies in dealing with separatist threats.